A new Mexican species of Megarthrus Curtis (Coleoptera, Staphylinidae, Proteininae) - Rodríguez, William David; Navarrete-Heredia, José Luis (Zootaxa, 2015)
The genus Megarthrus Curtis with about 140 species described, is the largest of the subfamily Proteininae (Coleoptera: Staphylinidae) (Cuccodoro 2011; López-García et al. 2011). It is distributed worldwide (Cuccodoro 1999) and has an amphipolar distribution, being more diverse in Holarctic region (Newton 1985). In the tropics, the ecological requirements of Megarthrus species restrict their presence to mountain areas, showing high levels of endemism, making a taxon potentially informative for biogeographic analysis (Cuccodoro 1998). In Mexico there was only one described  species: Megarthrus altivagans Bernhauer, 1929, but it is known that there are several undescribed species (Navarrete-Heredia et al. 2002). Cuccodoro (2011),  recognised “eleven species  from Mexico, eleven species from Costa Rica, Guatemala, Honduras, Nicaragua and Panama, and fifteen species from Bolivia, southern Brazil, Colombia, Ecuador, Peru and Venezuela”. In this paper we describe a new species of Mexican Megarthrus from the State of Jalisco.